2021
DOI: 10.7759/cureus.17510
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain Among School Teachers in Qassim, Saudi Arabia: Prevalence, Pattern, and Its Risk Factors

Abstract: Work-related musculoskeletal disorders (WMSD) are defined as conditions that the environment contributes significantly to / worsens due to work conditions. WMSD comes second in the source of disability in both developed and developing countries. The aim of this study is to measure the prevalence, patterns, and risk factors of musculoskeletal pain disorders among teachers in the Qassim region, Saudi Arabia. MethodsA cross-sectional study was conducted among school teachers in the Qassim region, Saudi Arabia. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
6
11
1
Order By: Relevance
“…Surprisingly, the females demonstrated a higher prevalence of MSDs than the males in all the body regions, almost twofold in some body regions, such as the wrists/hands. This is consistent with the finding of previous studies involving the teachers in Saudi Arabia: that the prevalence of MSDs among such teachers is 62.5–91% [ 15 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Surprisingly, the females demonstrated a higher prevalence of MSDs than the males in all the body regions, almost twofold in some body regions, such as the wrists/hands. This is consistent with the finding of previous studies involving the teachers in Saudi Arabia: that the prevalence of MSDs among such teachers is 62.5–91% [ 15 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study also indicate that the lower back (72.91%) and shoulders (66.93%) are the body regions most affected by MSDs among teachers. Similar results were found in previous studies on the prevalence of MSDs among Saudi teachers, indicating a lower back MSD prevalence of up to 74.4% [ 15 21 ]. Interestingly, in previous studies in Saudi Arabia, the prevalence of shoulder pain among teachers was found to range from 20.6% to 57.5%, slightly lower than in the current study [ 15 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations